Hyperammonemia syndrome due to Ureaplasma infection after liver‐kidney transplant. Issue 3 (30th April 2020) - Cannon, Chase A.; Corcorran, Maria A.; Shaw, Kathryn W.; Montenovo, Martin; Sibulesky, Lena; Reyes, Jorge D.; Rayhill, Stephen C.; Larson, Anne M.; Kritek, Patricia A.; Giovanni, Shewit; de Castro, Iris; Arora, Nayan; et al.
Abstract: Hyperammonemia syndrome, with high levels of ammonia and neurologic dysfunction, is a syndrome with historically high mortality that may occur after solid organ transplantation. Recently, this has been associated with infection due to Ureaplasma, mostly following lung transplantation. We describe the first case of hyperammonemia syndrome due to Ureaplasma infection after liver‐kidney transplantation. Our patient rapidly recovered after specific antibiotic treatment. It is important to consider these infections in the differential diagnosis for encephalopathy post‐transplant, as these organisms often do not grow using routine culture methods and polymerase chain reaction testing is typically required for their detection. This is particularly critical after liver transplantation, where a number of other etiologies may be considered as a cause of hyperammonemia syndrome.